Management of giant popliteal artery aneurysm using in situ saphenous vein bypass: A case report - Yümün, Gündüz; Haşimoğlu, Hakan (The European Research Journal, 2025)
Popliteal artery aneurysm is the most common type of peripheral artery aneurysm. These lesions are associated with atherosclerotic disease and other arterial aneurysms. The timing and approach of surgery are critical for limb preservation and reducing the risk of amputation in symptomatic cases. This case report presents our surgical approach, technique, and graft selection for a 75-year-old female patient with swelling and pain in the leg due to a giant popliteal artery aneurysm complicated by thrombosis. We bypassed the superficial femoral artery to the distal popliteal artery below the knee, using the in situ saphenous vein. We excluded the enlarged segment by ligating it at the anastomosis sites. In situ bypass is considered a highly effective method with excellent patency rates that minimizes surgical trauma in the treatment of popliteal aneurysms extending below the knee.